PELATIHAN PENULISAN ARTIKEL ILMIAH TERINDEKS SCOPUS - Rabiyatul Jasiyah; Saifullah Saifullah; Sitti Hasnah; Ferry WF Waangsir; Ratna Ayu Pawestri Kusuma Dewi; Mauritz Pandapotan Marpaung (Universitas Pahlawan Tuanku Tambusai, 2023)
Kegiatan ini menyajikan pelaksanaan